2002
DOI: 10.1002/art.10610
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐15 inhibits sodium nitroprusside–induced apoptosis of synovial fibroblasts and vascular endothelial cells

Abstract: Objective. One of the pathologic hallmarks of juvenile rheumatoid arthritis (JRA) is a tumor-like expansion of inflamed synovial tissue, or pannus, which causes much of the joint damage in this disease. The expansion of pannus is supported by extensive formation of new blood vessels. We have previously shown that revascularization of minced JRA synovial tissues engrafted into SCID mice correlated with the intensity of inflammatory activity in the tissues and with interleukin-15 (IL-15) expression. Since synovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Recently, a key role for IL-2 acting in synergy with IL-1β in facilitating IL-17 production has been confirmed in pulmonary γδ T cells 27 . While these observations contrast from the data showing the limiting role of IL-2 in IL-17 production 28,29 , they also stress the necessity to define cefazolin action in more complex context of IL-17-producing helper T cell (Th17 cell) subset. Demonstration of anti-inflammatory effects of cefazolin may expedite possible future drug repositioning.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, a key role for IL-2 acting in synergy with IL-1β in facilitating IL-17 production has been confirmed in pulmonary γδ T cells 27 . While these observations contrast from the data showing the limiting role of IL-2 in IL-17 production 28,29 , they also stress the necessity to define cefazolin action in more complex context of IL-17-producing helper T cell (Th17 cell) subset. Demonstration of anti-inflammatory effects of cefazolin may expedite possible future drug repositioning.…”
Section: Discussionmentioning
confidence: 72%
“…For example, previous reports indicate that endothelial cells express IL-15 receptors and that IL-15 signaling is involved in the formation of new vasculature. 22, 23 IL-15 has also been shown to exhibit anabolic influences over skeletal muscle cells in vitro. 24 Moreover, IL-15 signaling has been shown to function as a protective agent against cell death in several immune and non-immune cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compelling evidence from another study [30] demonstrated that IL-15 suppressed sodium nitroprussideinduced apoptosis in synovial fibroblast cultures and vascular endothelial cells grown on Matrigel whereas vascular endothelial growth factor (VEGF) and Angiopoietin-1 (Ang-1) production was unaffected. The results of this study [30] suggested that IL-15 could play a critical role in dampening the apoptotic cascade which could contribute to RA synovial apoptosis resistance [31] and stabilization of newly formed blood vessels [30] while also promoting RA synovial neoangiogenesis [32].…”
Section: Interleukin-15 (Il-15)mentioning
confidence: 96%
“…However, subsequent studies in RA showed that IL-15 synovial expression persisted even after TNFblockade [28] and although IL-15 employed at high doses was a pan-T cell growth factor [29] its inability to stimulate cytokine synthesis also indicated that IL-15 did not continuously drive antigen-specific T-cell proliferation [29]. Moreover, compelling evidence from another study [30] demonstrated that IL-15 suppressed sodium nitroprussideinduced apoptosis in synovial fibroblast cultures and vascular endothelial cells grown on Matrigel whereas vascular endothelial growth factor (VEGF) and Angiopoietin-1 (Ang-1) production was unaffected. The results of this study [30] suggested that IL-15 could play a critical role in dampening the apoptotic cascade which could contribute to RA synovial apoptosis resistance [31] and stabilization of newly formed blood vessels [30] while also promoting RA synovial neoangiogenesis [32].…”
Section: Interleukin-15 (Il-15)mentioning
confidence: 97%